Character Building in Pondok Pesantren Al-Ghurobaa' - Zafi , Ashif Az (LPPPM STAI Darul Hikmah Bangkalan, 2021)
This research aims to describe how the character building in Al-Ghurobaa's Pesantren. This research uses qualitative analysis. Data collection using interviews, observation, and documentation. The data were analyzed through the stages of data reduction, data presentation, and concluding. The findings in this study are that character building begins with building the social structure of the pesantren. The social structure of the pesantren is made through three stages, namely making rules, enforcing rules, and habituating the rules. The contribution of this research is helpful for pesantren who want to build character. Pesantren can imitate the pattern done at Al-Ghurobaa's Pesantren.